Learning Mathematics in the Digital Era: An Analysis of High School Students’ Interaction Patterns through TikTok - Putri Putri; Nursupiamin Nursupiamin; Yulia Yulia (STKIP Singkawang, 2026)
The rapid growth of social media has reshaped students’ learning behaviors and interaction patterns, including in mathematics education. TikTok, as a short-form video platform widely used by adolescents, offers unique affordances for micro-learning, algorithm-driven content exposure, and non-linear interaction. Although previous studies have demonstrated that TikTok can improve students’ mathematics achievement, motivation, and interest, limited attention has been paid to the underlying social-cognitive interaction processes through which mathematical understanding is constructed. This study aims to analyze high school students’ interaction patterns in learning mathematics through TikTok by examining how digital interactions support mathematical sense-making rather than merely learning outcomes.This study employed a descriptive qualitative approach involving four eleventh-grade students at MAN 2 Palu, Indonesia, selected through purposive sampling. Data were collected through observations of students’ TikTok activities and semi-structured interviews. The analysis was guided by Moore’s interaction model, encompassing student–content, student–creator interactions, and student–student interactions, adapted to the non-linear and algorithmic context of TikTok. The findings reveal three distinct interaction patterns: high, moderate, and low. Students with high interaction levels actively engaged across all three interaction dimensions, demonstrating reflective learning, digital self-efficacy, and autonomous regulation of mathematical learning. In contrast, students with moderate and low interaction levels primarily engaged in passive content consumption, with limited social and pedagogical interaction, positioning TikTok more as an entertainment platform than a learning space. These differences indicate that mathematical sense-making on TikTok is strongly mediated by the quality of interaction rather than the intensity of platform use alone. This study highlights that TikTok’s educational potential lies not merely in its effectiveness in improving scores, but in how interaction quality shapes students’ cognitive engagement and meaning-making processes in mathematics learning. The findings suggest that integrating structured interaction designs and fostering digital self-efficacy are crucial for maximizing the pedagogical value of social media-based mathematics learning.Pembelajaran Matematika di Era Digital: Analisis Pola Interaksi Peserta Didik SMA melalui Media TikTokABSTRAKPerkembangan media sosial telah mengubah cara siswa mengakses, memaknai, dan berinteraksi dengan pengetahuan matematika. TikTok, sebagai platform video pendek berbasis algoritma, menawarkan karakteristik pembelajaran yang berbeda dari platform digital konvensional karena menggabungkan konten ringkas, atensi cepat, serta interaksi sosial yang bersifat spontan dan tidak linier. Namun, masih terbatas penelitian yang menjelaskan bagaimana pola interaksi siswa di TikTok berkontribusi terhadap proses mathematical sense-making, bukan sekadar peningkatan hasil belajar. Penelitian ini bertujuan untuk menganalisis pola interaksi siswa SMA dalam pembelajaran matematika melalui TikTok dengan menggunakan Model Interaksi Moore yang mencakup student–content, student–creator interaction, dan student–student interaction. Penelitian menggunakan pendekatan kualitatif deskriptif dengan empat siswa kelas XI MAN 2 Kota Palu yang dipilih melalui teknik purposive sampling. Data dikumpulkan melalui observasi aktivitas TikTok dan wawancara semi-terstruktur, kemudian dianalisis secara tematik. Hasil penelitian menunjukkan tiga kategori pola interaksi, yaitu tinggi, sedang, dan rendah. Siswa dengan interaksi tinggi aktif pada ketiga dimensi Moore, memanfaatkan fitur TikTok seperti video pendek, komentar, Live, dan pesan langsung untuk membangun pemahaman konsep, merefleksikan strategi penyelesaian soal, serta mendiskusikan ide matematika secara kolaboratif. Sebaliknya, siswa dengan interaksi rendah cenderung hanya mengakses konten secara pasif dan tidak terlibat dalam proses negosiasi makna matematis. Temuan ini menunjukkan bahwa perbedaan kualitas interaksi digital berpengaruh signifikan terhadap cara siswa membangun pemahaman matematika di lingkungan media sosial. Disimpulkan bahwa keunikan TikTok sebagai ruang belajar tidak terletak pada kontennya semata, melainkan pada pola interaksi sosial-kognitif yang terbentuk melalui integrasi algoritma, micro-learning, dan jejaring sosial. Penelitian ini menegaskan pentingnya menggeser fokus kajian dari efektivitas hasil belajar menuju analisis proses interaksi digital sebagai kunci pengembangan pembelajaran matematika berbasis media sosial.Kata Kunci :pola interaksi; pembelajaran matematika; siswa SMA; TikTok